Effects of different break activities on recovery from mental fatigue - Ng, Melody Mun Hoong (2016)
The purpose of the study was to investigate the effects of a break including light intensity physical activity on the recovery from mental fatigue. It is hypothesized that a short bout of physical activity during a break would have a positive effect on the recovery of mental fatigue compared to just remaining seated and reading. This research consists of two main studies; (1) Workplace Sitting Breaks Questionnaire (SITBRQ) conducted in a local company with 100 responses and (2) Controlled Experiment with 20 sedentary participants (10 male, 10 female; M age = 23.8 years, SD = 1.64; M body mass index = 21.6 kg/m2, SD = 2.46) who were tested by inducing mental fatigue through Digit Span Test and assessing their recovery from mental fatigue after a break through cognitive performance assessments such as Stroop Test, Math Fluency Test (MFT) and Remotes Associates Test (RAT). Self-reporting scales for fatigue levels and Positive Affect and Negative Affect Schedule (PANAS) were also administered. The results for Study 1: SITBRQ showed that 30% of the staff only took less than 5 minutes of short physical activity breaks. Findings for Study 2: Controlled Experiment showed that the main effects of time (p = <.001) and conditions (p = .033) for MFT scores were significant, suggesting improvements in recovery of retrieving storage memory after walking during a break. In conclusion, the results of the study support taking a short walk during a break to increase mental fatigue recovery.